The totality of change-in-control payments - Offenberg, David; Officer, Micah S. (Journal of Corporate Finance, 2014)
Most extant studies consider golden parachutes as the totality of change-in-control payments. However, for the median CEO of firms listed in the S&P SmallCap 600 index in 2009, golden parachute payments are only 46% of total change-in-control compensation. We measure total change-in-control payments using newly available data for this sample. Our results show that the total payments to the departing CEO are estimated at 1.1% of market value (on average). We also show that newly earned compensation (as opposed to accelerated vesting of lagged incentive pay) makes up approximately half of total change-in-control payments for the median CEO, and these two components of severance pay are positively correlated (contrary to existing theory). Furthermore, change-in-control payments do not appear to impede takeover offers or affect takeover premiums. Total change-in-control payments are small on average, and boards seem to take care in negotiating these terms with incumbent CEOs so that change-in-control payments do not adversely affect the firm's prospects in the takeover market.